A re-assessment of ornament as a sculptural element - Chetwin, Margaret Jill (Michaelis School of Fine Art, 2023)
This dissertation partial 2 and photographic documentation was produced in fulfilment of the requirements for the Degree of Master of Fine Arts (MFA) at the Michaelis School of Fine Art, University of Cape Town. In my undergraduate study I was interested in the way in which familiar objects changed their meaning in different contexts. In this study, my focus of attention has been on the transference of meaning associated with the conventionalised language of historical ornament. This has involved a process of incorporating 'found' imagery into composite images of a fantastical nature. The use of ornament as a source material posed problems. The original symbolic function and communicative power of many ornamental motifs and images has been undermined by constant use. As such they have become cliched. I have attempted to revitalise these tired forms through a re-assessment of their value as 'sculptural' elements and by an ironical examination of their past associations. Before re-contextualising the work in a contemporary dimension, it was necessary to undertake a survey of the historical antecedents of revivalism and other forms of aesthetic eclecticism. Although schematic, this overview was important to my understanding, and I have devoted a full chapter of the dissertation to this section of the study. A discussion of current Post-Modern debates is included and forms a central part of this section.